Evaluation of medication adherence in hypertensive patients and influential factors - Boratas, Selma; Kilic, Hulya Firat (Professional Medical Publications, 2018)
Objective: This study aims to evaluate medication adherence in hypertensive patients and to identify the influential factors. Methods: This descriptive, cross-sectional study included a total of 147 hypertensive patients who were admitted to Akdogan Health Center between December 2016 and February 2017. The Descriptive Data Form and Medication Adherence Self-Efficacy Scale were used as the data collection tools. Results: The mean Medication Adherence Self-Efficacy Scale score was found to be 70.29 +/- 8.52. Age, duration of HT, the frequency of follow-up visit for HT, the status of taking medication regularly, the frequency of blood pressure measurement and the status of alternative method use were found to be effective in medication adherence. Conclusions: Our study results suggest that medication adherence is good in patients with hypertension ( HT). Factors which are effective in medication adherence should be taken into consideration, when evaluating the medication adherence in patients with HT.
Keywords: Adherence; Hypertension; Medication; Patients